Evaluation of Gadopiclenol and P846, 2 High-Relaxivity Macrocyclic Magnetic Resonance Contrast Agents Without Protein Binding, in a Rodent Model of Hepatic Metastases: Potential Solutions for Improved Enhancement at Ultrahigh Field Strength. Issue 9 (September 2019) - Fries, Peter; Massmann, Alexander; Robert, Philippe; Corot, Claire; Laschke, Matthias W.; Schneider, Günther; Buecker, Arno; Müller, Andreas
Abstract : Purpose: The aim of this study was to evaluate in vitro and in vivo the enhancement properties of experimental gadolinium (Gd)-based contrast agents (GBCAs) with different molecular weights and hydration numbers (P846 and gadopiclenol) compared with clinically approved low-molecular, extracellular agents (gadopentetate and gadoterate) at 9.4 T and to discuss influencing factors on r1 relaxivities. Methods and Materials: All experiments were performed with a 9.4 T animal scanner (Bruker, Germany). We performed relaxometry measurements for all contrast agents in human plasma at 37°C using an IR-RARE sequence. In addition, we compared P846 with gadopentetate and gadopiclenol with gadoterate intraindividually in rats with hepatic colorectal cancer metastases (n = 10 each) acquiring T1-weighted FLASH sequences before and at 10 consecutive time points during 20 minutes. After intravenous contrast agent application, signal-to-noise ratios (SNRs), contrast-to-noise ratios (CNRs), and lesion enhancement (LE) for liver parenchyma and tumors were calculated based on region of interest measurements. Results: Longitudinal relaxivities (r1) of the low-molecular agents were lower as compared with the experimental compounds. However, r1 of gadopentetate and gadoterate demonstrated only a moderate decrease of r1 at 9.4 T as compared with known data at lower field strengths (gadopentetate: r1 [at 9.4 T], 3.4 mM −1 s −1 /r1 [at 1.5 T], 4.1 mM −1 s −1 /gadoterate: r1 [at 9.4 T], 3.1 mM −1 s −1 /r1 [at 1.5 T], 3.6 mM −1 s −1 ). In contrast, r1 of P846 showed a marked reduction at 9.4 T compared with 1.5 T (P846: r1 [at 9.4 T], 6.4 mM −1 s −1 /r1 [at 1.5 T], 32 mM −1 s −1 ). Gadopiclenol provided the highest r1 in this study at 9.4 T and the drop of r1 as compared with lower field strength is less apparent (gadopiclenol: r1 [at 9.4 T], 8.7 mM −1 s −1 /r1 [at 1.5 T], 12.7 mM −1 s −1 ). In vivo, P846 and gadopiclenol showed significantly higher SNR, CNR, and LE as compared with the low-molecular control agents (mean ± SD; SNRliver [gadopentetate, 18.1 ± 1.2; P846, 27.2 ± 1.5; P < 0.001]; SNRtumor [gadopentetate, 22.6 ± 1.9; P846, 40.1 ± 1.9; P < 0.001]; CNR [gadopentetate, 4.6 ± 1.0; P846, 12.9 ± 0.9; P < 0.001]; LE [gadopentetate, 7.2 ± 1.9; P846, 14.9 ± 1.9; P < 0.001]/SNRliver [gadoterate, 8.8 ± 0.5; gadopiclenol, 12.6 ± 1.3; P < 0.001]; SNRtumor [gadoterate, 11.3 ± 1.2; gadopiclenol, 20.9 ± 2.9; P < 0.001]; CNR [gadoterate, 2.5 ± 0.7; gadopiclenol, 8.3 ± 1.7; P < 0.001]; LE [gadoterate, 4.4 ± 1.2; gadopiclenol, 13.0 ± 2.9; P < 0.001]). Thus, for equal Gd doses, gadopiclenol and P846 increase the CNR of liver metastases by a factor of 2.5 to 3 at 9.4 T compared with gadoterate and gadopentetate. Conclusions: P846 and gadopiclenol provide superior enhancement at 9.4 T as compared with gadopentetate and gadoterate. However, the macromolecular agent P846 shows a marked decrease of r1 from 1.5 T to 9.4 T. This effect is less apparent for the low-molecular agents gadopiclenol, gadopentetate, and gadoterate. Yet, based on the higher hydration number, r1 of P846 and gadopiclenol are markedly higher as compared with the reference contrast agents. Thus, building compounds with moderately increased molecular size and hydration number, as implemented in gadopiclenol, seems to be a promising way to develop highly effective GBCAs. Advantages for gadopiclenol include a strong enhancement regardless of the external magnetic field strength, pharmacokinetics comparable to those of clinically approved extracellular GBCAs, and the potential to either improve sensitivity in diagnostic magnetic resonance imaging by improving lesion conspicuity or to perform studies with significantly reduced Gd-dose while at the same time providing comparable diagnostic accuracy. However, all this needs to be proven in clinical studies.